Acid hydrolysis of chitin in calcium chloride solutions. Issue 7 (7th February 2023) - Wang, Yudi; Kou, Jia; Wang, Xuewei; Chen, Xi
Abstract : This work describes a mild aging-hydrolysis integrated approach to selectively produce N -acetyl-d -glucosamine from chitin in cheap and abundant CaCl2 -based molten salt hydrate solvents. Abstract : Chitin hydrolysis is an important but challenging reaction for shell biorefineries. In this study, we devised a mild aging-hydrolysis integrated approach to selectively produce N -acetyl-d -glucosamine (NAG) from chitin in cheap and abundant CaCl2 -based molten salt hydrate solvents (MSHs). The acid-aged chitin could be directly employed and hydrolyzed in 50 wt% CaCl2 solution at 393 K for 1 h, producing NAG in 51.0% yield, which was further improved to 66.8% with the addition of ZnBr2 (10 wt%) as a co-salt. The synergy of aging and the CaCl2 MSHs was critical for the efficient chitin hydrolysis. A significant decrease of chitin's molecular weight was observed after aging at near room temperature, while the CaCl2 MSHs enabled chitin swelling and dissolution to facilitate the substantial cleavage of glycosidic bonds during the hydrolysis reaction. The combined contrast experiments, TOF-MS, XPS, and NMR studies revealed that both the Ca 2+ cation and the Cl − anion have closely interacted with the chitin chains primarily by coordinating with the carbonyl oxygen/amido nitrogen atoms or by forming hydrogen bonds with the –OH groups, respectively, which could alter the electrostatic states of the chitin chains and favor the hydrolysis.